Volleyball training and practice: vertical jump and agility tests - Altin Martiri; Enkeleida Lleshi (Universidad de Murcia, 2024)
This study aimed to research peculiarities of improving high jump techniques training in modern volleyball and developing agility amongst sportsmen in the context of attributive components, that influence the success of team competition plays. The methodological basis of this study consists of methods of systematic analysis of key components in distributing training loads amongst volleyball team members on a stage of pre-season training with complex research of various aspects of jumping ability and agility of sportsmen tests employment and their practical use on the stage of preparing sportsmen in the competitive period as well. The results of the study showed the high practical importance of testing the real jumping and agility characteristics of volleyball players and show prospects for the practical use of the test system for these characteristics at the training level of athletes in order to achieve high fitness of sports commands and successful games in monthly competitions. The practical benefit of these results obtained during the research lies in the ability to use them in the training process of modern volleyball teams to develop the agility and jumping abilities of athletes, which has prospects for higher results of sports teams in competitions.